Leveraging the ASSURE Model for Optimized Information Technology-Based Learning Media - Eliana, Neneng; Wati, Unik Ambar; Rahmadona, Sisca (STAI Hubbulwathan Duri, 2024)
The evaluation of technology-based learning media is crucial in modern education to ensure its effectiveness in improving student learning outcomes and addressing various challenges. This study aims to evaluate the effectiveness of information technology-based learning media in Class VI of SD Negeri 07 Angkasa using the ASSURE model. A case study approach was employed, involving 1 teacher and 10 sixth-grade students. Data were collected through interviews, observations, and documentation. The analysis followed the stages of data reduction, data display, and conclusion drawing. The findings revealed that the teacher used PowerPoint, Word Wall, and Quizizz Paper Mode, resulting in a 50% increase in student engagement and a 21.43% improvement in student performance. Key factors supporting the use of technology-based learning media included school facilities such as modems, WiFi cards, projectors, laptops, and speakers, as well as teachers' personal smartphones. However, challenges included limited internet access and unstable electricity. Solutions such as using offline technology, portable hotspots, backup power sources, and devices with sufficient battery life were suggested. The integration of information technology-based learning media showed positive effects on student engagement and performance. However, infrastructure limitations, curriculum alignment, and time management issues need to be addressed to optimize its use. This study concludes that the application of information technology-based learning media using the ASSURE model positively impacts student learning processes and outcomes. Overcoming infrastructural and logistical challenges is necessary to enhance its effectiveness in classrooms.